Thermal performance in a tubular heat exchanger with deltawinglets - Pattarapan Tongyote; Pongjet Promvonge; Nattawoot Depaiwa; Withada Jedsadaratanachai (My University, 2018)
The paper presents an experimental heat transfer enhancement study in a tubular heat exchanger fitted with delta-winglets. The experimental work was conducted by varying the airflow rate in the test tube having a constant wall heat-flux for turbulent regime, Reynolds number (Re) from 5200 to 23,000. Effects of three pitch ratios (PR=P/D=1.5, 2.0 and 3.0) and two attack angles, α = 45° and 60°, of the winglets at a single blockage ratio (BR=b/D = 0.15) on thermal characteristics are examined. The experimental results show that the winglet-inserted tube yields, respectively, the heat transfer, friction factor and thermal performance in the form of TEF around 1.99–4.08, 4.9–14.3 times higher than the plain tube and 0.85–1.85, depending on the operating condition.
Keywords: Wingtip device; Heat Transfer Mechanisms